2013
DOI: 10.1002/jae.2312
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Gasoline: Evidence From Household Survey Data

Abstract: SUMMARY In this paper we investigate the demand for gasoline in Canada using recent annual expenditure data from the Canadian Survey of Household Spending, over a 13‐year period from 1997 to 2009, on three expenditure categories in the transportation sector: gasoline, local transportation, and intercity transportation. In doing so, we use three of the most widely used locally flexible functional forms, the Almost Ideal Demand System (AIDS) of Deaton and Muellbauer (1980), the quadratic AIDS (QUAIDS) of Banks e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…We acknowledge that by focusing explicitly on the electricity market we are not modeling a complete demand system, as has recently been done by Serletis and Shahmoradi (2008) and Serletis et al (2010a) for 2 While many of the studies on electricity demand focus on residential demand (e.g., Halvorsen, 1975;Maddala et al, 1997;Silk and Joutz, 1997), there have also been studies on the channels of electricity usage in the commercial and industrial sectors (e.g., Berndt and Wood, 1975;Halvorsen, 1978; or more recently Bernstein and Madlener, 2010;Pielow et al, 2012). the US energy market, Serletis et al (2010bSerletis et al ( , 2011 for energy markets across a panel of OECD and non-OECD countries, and Chang and Serletis (2014) for the Canadian transportation sector. Reducing a demand system to a single equation has at least two drawbacks.…”
Section: Benchmark Modelsmentioning
confidence: 99%
“…We acknowledge that by focusing explicitly on the electricity market we are not modeling a complete demand system, as has recently been done by Serletis and Shahmoradi (2008) and Serletis et al (2010a) for 2 While many of the studies on electricity demand focus on residential demand (e.g., Halvorsen, 1975;Maddala et al, 1997;Silk and Joutz, 1997), there have also been studies on the channels of electricity usage in the commercial and industrial sectors (e.g., Berndt and Wood, 1975;Halvorsen, 1978; or more recently Bernstein and Madlener, 2010;Pielow et al, 2012). the US energy market, Serletis et al (2010bSerletis et al ( , 2011 for energy markets across a panel of OECD and non-OECD countries, and Chang and Serletis (2014) for the Canadian transportation sector. Reducing a demand system to a single equation has at least two drawbacks.…”
Section: Benchmark Modelsmentioning
confidence: 99%
“…One important parameter for determining the consequences of crude oil price shocks for the macroeconomy is the price elasticity of the demand for gasoline [22]. As shown in Table 1, the demand for gasoline has been investigated extensively using different methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the normalized quadratic (NQ) method is applied to examine inter-fuel substitution elasticities at the sector and aggregate levels [23,24]. By employing Canadian household survey data and using three of the flexible functional forms (the Almost Ideal Demand System (AIDS), the Quadratic AIDS (QUAIDS) and the Minflex Laurent model), Chang and Serletis estimate that the own-price elasticity for gasoline demand in the transportation sector is between 0.738 and 0.570 [22]. …”
Section: Introductionmentioning
confidence: 99%
“…As we discussed in the literature review that earlier studies (e.g. Kayser, ; Gundimeda and Köhlin, ; Wadud et al ., ; Chang and Serletis, ) in other countries have revealed that many demographic factors (e.g. driver's age, gender, education level, household size, race, location, etc.)…”
Section: The Research Hypothesismentioning
confidence: 99%